An Analysis Of Smart City Mission And Its Approach In Housing Need Towards Slum Dwellers In India - et. al., Yogita Nagpure , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Smart Cities Project has introduced by Indian government. During this mission the Indian government has set a goal of developing 100 smart cities by 2022. It is absolutely true that smart city varies from different city to city, country to country and it all depends on the culture and tradition in the particular state or city. The main aim of smart city mission is to promote sustainable and inclusive cities that help to deliver essential infrastructure and the respectable life to their people. Several literatures indicate that the SCM has ignored its self-claimed inclusive planning process. They have ruthlessly and disrespectfully evicted slum population from cities without adequate consultation. This paper will assess how inclusive the SCM planning process was in dealing with slums residents living in the town. Housing and inclusiveness are among those most critical features which expands housing options for all. Design methodology for this research will be based on examining secondary literature in the form of development. It also studied inclusiveness, citizen grievance redressal, citizen engagement, open/democratic participation and transparency, human rights, viewpoints, development policies, policies in India. This research helps to identify how fair and inclusive the SCM was in dealing with slum population living in the city and offer recommendations for inclusive smart city policy development. This research limits to various Smart City Mission’s development and investigate slum sufferers’ issues related to their displacement and evictions. This research will help to do sequentially streamline the smart city development process to ensue social justice to poor and weaker section of the society living in cities.